2009
DOI: 10.1111/j.1600-0765.2008.01131.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of C‐reactive protein and interleukin‐6 in plasma of patients with aggressive periodontitis

Abstract: Patients with aggressive periodontitis have significantly elevated levels of plasma C-reactive protein and interleukin-6. These elevated inflammatory factors might potentially increase the risk for cardiovascular events and glucose dysregulation in relatively young individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 36 publications
4
43
1
5
Order By: Relevance
“…For example, Glurich (Glurich et al 2002), reporting data from the Erie County Periodontal Epidemiology Study, noted a hierarchy in levels of CRP, serum amyloid A and alpha 1-antichymotrypsin, wherein the highest levels were found in patients with both periodontitis and CVD compared to either condition alone. Other markers such as ceruloplasmin and sVCAM-1 were elevated only in CVD Serum levels increased in chronic periodontitis (CP) Ebersole et al 1997, Loos et al 2000, Slade et al 2000, Noack et al 2001, Offenbacher 2002, Ebersole et al 2002, Buhlin et al 2003, Beck and Slade et al 2003, Amar et al 2003, Yoshii et al 2009, Gomes-Filho et al 2011, Pejcic et al 2011, Serum levels increased in aggressive periodontitis Salzberg et al 2006, Sun et al 2009, Serum levels increased in patients with CVD and CP compared to either condition alone Glurich et al 2002, Persson et al 2005, Amabile et al 2008, Malali et al 2010, Liu et al 2010 PAF levels elevated in serum and gingiva, PAF-AH levels decrease following therapy Noguchi et al 1989, Losche et al 2005, Zheng et al 2006, Chen et al 2010 while some including sICAM-1 were not elevated. Similar observations have since been made in other populations, including a Chinese population with relatively low CRP concentrations (Liu et al 2010).…”
Section: C-reactive Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Glurich (Glurich et al 2002), reporting data from the Erie County Periodontal Epidemiology Study, noted a hierarchy in levels of CRP, serum amyloid A and alpha 1-antichymotrypsin, wherein the highest levels were found in patients with both periodontitis and CVD compared to either condition alone. Other markers such as ceruloplasmin and sVCAM-1 were elevated only in CVD Serum levels increased in chronic periodontitis (CP) Ebersole et al 1997, Loos et al 2000, Slade et al 2000, Noack et al 2001, Offenbacher 2002, Ebersole et al 2002, Buhlin et al 2003, Beck and Slade et al 2003, Amar et al 2003, Yoshii et al 2009, Gomes-Filho et al 2011, Pejcic et al 2011, Serum levels increased in aggressive periodontitis Salzberg et al 2006, Sun et al 2009, Serum levels increased in patients with CVD and CP compared to either condition alone Glurich et al 2002, Persson et al 2005, Amabile et al 2008, Malali et al 2010, Liu et al 2010 PAF levels elevated in serum and gingiva, PAF-AH levels decrease following therapy Noguchi et al 1989, Losche et al 2005, Zheng et al 2006, Chen et al 2010 while some including sICAM-1 were not elevated. Similar observations have since been made in other populations, including a Chinese population with relatively low CRP concentrations (Liu et al 2010).…”
Section: C-reactive Proteinmentioning
confidence: 99%
“…Further studies have provided evidence for elevated systemic levels of additional proinflammatory mediators and markers in chronic periodontitis (CP) including fibrinogen, haptoglobin, and IL-18, as well as decreased levels of anti-inflammatory mediators including IL-4 (Buhlin et al 2009). Furthermore, CRP levels may be elevated in sera from patients with AgP based on two studies (Salzberg et al 2006, Sun et al 2009). …”
Section: C-reactive Proteinmentioning
confidence: 99%
“…[111213141516] Since both forms of periodontitis show disparity in the rate of progression, the effect of chronic and aggressive periodontitis on CRP levels seems to be an appealing area of research. Thus, the present study was undertaken to determine the relative levels of serum CRP and compare them in aggressive and chronic periodontitis patients and correlating the serum CRP levels with severity of disease.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, accumulated evidence has demonstrated the association between periodontitis and CRP. The serum CRP is increased in systemically healthy subjects with periodontitis [46]. It was reported that subjects with periodontitis had 1.65 mg/L higher serum CRP compared with individuals without periodontitis [47].…”
Section: Effect Of Periodontal Intervention On C-reactive Proteinmentioning
confidence: 99%